menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Suppose a - b = 0a−b=0a, minus, b, equals, 0. Which one of these expressions equals ababa, b?
asked
Dec 27, 2019
130k
views
2
votes
Suppose a - b = 0a−b=0a, minus, b, equals, 0. Which one of these expressions equals ababa, b?
Mathematics
middle-school
Sankha Jayalath
asked
by
Sankha Jayalath
5.6k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
4
votes
ab=a² and ab=b².
Since a-b=0, this means that a=b.
For ab, we can rewrite this as a*a, which is a².
We can also write this as b*b, which is b².
Sarat Patel
answered
Dec 31, 2019
by
Sarat Patel
5.5k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.9m
questions
7.7m
answers
Other Questions
Solve for y in terms of x. 2/3y - 4 = x y = x + 6 y = -x + 4 y = -x + 6 y = x + 4
Aliyah has $24 to spend on seven pencils. After buying them she had $10. How much did each pencil cost?
Use the normal model n(11371137,9696) for the weights of steers. a) what weight represents the 3737thth percentile? b) what weight represents the 9999thth percentile? c) what's the iqr of the weights
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org